RA4Self-CPS: A Reference Architecture for Self-adaptive Cyber-Physical Systems - Camargo, Marcos Paulo De Oliveira [UNESP]; Pereira, Gabriel Dos Santos [UNESP]; Almeida, Daniel [UNESP]; Bento, Leandro Apolinário [UNESP]; Dorante, William Fernande [UNESP]; Affonso, Frank José [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Cyber-Physical Systems (CPS) represent an evolution of embedded systems by the computational elements interacting with physical entities through a network. Self-adaptive Cyber-Physical Systems (Self-CPS) present specific features compared to traditional CPS because this type of system can deal with changes at runtime. In parallel, Reference Architectures (RA) enable reusable artifacts that aggregate the knowledge of software architectures in specific domains. RAs have facilitated the development, standardization, and system evolution in different domains. Despite their relevance, reference architectures that could support the more systematic development of Self-CPS, covering issues like self-protecting and observability, are not found yet. Based on this scenario, the main contribution of this paper is to present an RA for Self-CPS named RA4Self-CPS. The goal of this RA is to support the Self-CPS development that requires self-protecting, observability, and adaptation at runtime. To show the viability of our RA, we conducted a case study that revealed a good perspective to contribute to the Self-CPS area.
Keywords: cyber-physical systems; reference architecture; self-adaptive; self-CPS